DALUWARSA PENUNTUTAN PERSFEKTIF KEPASTIAN DAN KEADILAN HUKUM (PERBANDINGAN KUHP LAMA, KUHP BARU, DAN KANUN KESEKSAAN MALAYSIA) - ristanti, yuni; Louk Fanggi , Prandy Arthayoga (Fakultas Hukum Universitas Gunung Rinjani, 2025)
This study explores the position of the statute of limitations in criminal prosecution within the legal systems of Indonesia and Malaysia, focusing on the tension between legal certainty and justice. The statute of limitations limits the time within which the state can prosecute a criminal offender. In Indonesia, including its 2023 Penal Code, there is still a time limit of up to 20 years even for serious crimes like murder. Conversely, Malaysia adopting the common law system does not impose any time limitation on the prosecution of criminal offenses, including murder. This comparison reveals fundamental differences between the civil law and common law traditions. Using a normative juridical method with statutory, comparative, and conceptual approaches, the study finds that limiting prosecution time may lead to injustice for victims of serious crimes. Therefore, it is recommended that Indonesia eliminate the statute of limitations for severe crimes, as a form of commitment to human rights protection and substantive justice. Such a move is also supported by advancements in forensic and digital evidence that allow for fair adjudication of older cases. Eliminating time limits in prosecuting serious crimes better aligns the law with the fundamental right to life and justice. Keywords: statute of limitations, legal certainty, legal justice, murder, legal system comparison